2010
DOI: 10.5194/bg-7-2959-2010
|View full text |Cite
|
Sign up to set email alerts
|

Carbon isotopic composition of branched tetraether membrane lipids in soils suggest a rapid turnover and a heterotrophic life style of their source organism(s)

Abstract: Abstract. Branched Glycerol Dialkyl Glycerol Tetraethers (GDGTs) are membrane spanning lipids synthesised by as yet unknown bacteria that thrive in soils and peat. In order to obtain more information on their ecological niche, the stable carbon isotopic composition of branched GDGT-derived alkanes, obtained upon ether bond cleavage, has been determined in a peat and various soils, i.e. forest, grassland and cropland, covered by various vegetation types, i.e., C 3 -vs. C 4 -plant type. These δ 13 C values are c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
102
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(114 citation statements)
references
References 67 publications
11
102
1
Order By: Relevance
“…Water saturation was also suggested to play a significant role for brGDGT abundance in African soils (Loomis et al, 2011). BrGDGT source organisms have been suggested to be heterotrophic (e.g., Weijers et al, 2010;Huguet et al, 2012;Opperman et al, 2012;Ayari et al, 2013), which could explain the higher brGDGT abundances coupled to high TOC. Earlier studies showed that brGDGT abundances are usually high in water-saturated soils and peat bogs, thus potentially providing an ideal environment for brGDGT source organisms that have been proposed to be anaerobic (Weijers et al, 2006).…”
Section: Brgdgt Abundances and Distributionmentioning
confidence: 96%
“…Water saturation was also suggested to play a significant role for brGDGT abundance in African soils (Loomis et al, 2011). BrGDGT source organisms have been suggested to be heterotrophic (e.g., Weijers et al, 2010;Huguet et al, 2012;Opperman et al, 2012;Ayari et al, 2013), which could explain the higher brGDGT abundances coupled to high TOC. Earlier studies showed that brGDGT abundances are usually high in water-saturated soils and peat bogs, thus potentially providing an ideal environment for brGDGT source organisms that have been proposed to be anaerobic (Weijers et al, 2006).…”
Section: Brgdgt Abundances and Distributionmentioning
confidence: 96%
“…The increased supply of ammonia and CO 2 may therefore facilitate the flourish of crenarchaeota, leading to higher abundance of crenarchaeol in organic-rich soils. The bGDGT-producing bacteria were believed to be heterotrophic [31]. Higher abundance of organism in soils may provide more nutrients for bacterial regeneration, leading to a higher production of bGDGTs.…”
Section: Ptocmentioning
confidence: 99%
“…Branched glycerol dialkyl glycerol tetraethers (brGDGTs) (see Schouten et al, 2013 for the review) are membrane-spanning lipids, most likely derived from anaerobic (Weijers et al, 2006a) and heterotrophic (Pancost and Sinninghe Damsté, 2003;Oppermann et al, 2010;Weijers et al, 2010) bacteria that occur ubiquitously in peat (e.g., Weijers et al, 2006a) and soil (e.g., Weijers et al, 2007a) as well as in lacustrine/marine sediments and water column (e.g., Blaga et al, 2009;Peterse et al, 2009a;Tierney and Russell, 2009;Pearson et al, 2011;Loomis et al, 2014;Weijers et al, 2014). The brGDGTs contain four to six methyl groups and up to two cyclopentane moieties formed by internal cyclization (Sinninghe Damsté et al, 2000;Weijers et al, 2006a, see Figure 1 for chemical structures).…”
Section: Introductionmentioning
confidence: 99%